Efficient cooperative image transmission in one-way multi-hop sensor network. Issue 4 (October 2020) - Al-Hayani, Bilal; Ilhan, Haci
The challenging task while transmitting the high-quality images over the wireless sensor networks is to achieve the higher throughput, minimum bit error rate without compromising the image quality. As the sensor nodes have the limited processing power, designing energy efficient image transmission is another challenge in this research. This paper proposed a novel method of cooperative image transformation from the transmitter to the receiver for wireless sensor networks. We designed the methods for multi-hop one-way relayed cooperative communication model for wireless sensor networks. We believe that the cooperative communication helps to improve the efficiency of image transmission. The proposed approach focused on efficient relayed image transmission through wireless channels with optimum image quality and bit error rate performances. First, lightweight image quality improvement method was proposed at both transmitter and receiver end as images captured under various illumination conditions. Second, the proposed compressive sensing was performed using the approximation coefficient of 2D discrete wavelet transform. We utilized the wavelet denoising advantage by presenting the hybrid thresholding function. And third, use of decode–forward method at relay nodes to perform the task of decode and forward received image data block. The compressed approximation component of 2D discrete wavelet Transform is further used to apply inverse fast Fourier transform and then in modulation using quadrature phase shift keying to transmit over additive white Gaussian noise channel to relay nodes as per the standard orthogonal frequency-division multiplexing model. The simulation results claim the performance efficiency against the state-of-art methods based on mean square error, peak signal-to-noise ratio, and bit error rate.